2016
DOI: 10.1016/j.jconrel.2016.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillar cellulose wound dressing in skin graft donor site treatment

Abstract: Based on the preliminary clinical data, NFC dressing seems to be promising for skin graft donor site treatment since it is biocompatible, attaches easily to wound bed, and remains in place until donor site has renewed. It also detaches from the epithelialized skin by itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
149
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(166 citation statements)
references
References 51 publications
7
149
0
2
Order By: Relevance
“…The possibility to create NFC‐based dressings for wound healing applications has been introduced and examined in a series of studies by ourselves and others, with promising results. However, to date, no work has addressed neither the hemocompatibility aspect of NFC‐based materials, nor the possibility of modifying these materials to obtain dressings that aid the first phase of wound healing—hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to create NFC‐based dressings for wound healing applications has been introduced and examined in a series of studies by ourselves and others, with promising results. However, to date, no work has addressed neither the hemocompatibility aspect of NFC‐based materials, nor the possibility of modifying these materials to obtain dressings that aid the first phase of wound healing—hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In this clinical study, the dressings were found to be highly biocompatible in the treatment of skin graft donor sites. According to preliminary comparison studies with SUPRATHEL, epithelialization rate was faster with nanofibrillar cellulose dressing . Recently, the bone healing tendency of a nanocomposite (DBSint) constituted of biomimetic nanostructured Mg‐hydroxyapatite and human demineralized bone matrix was approved for clinical use.…”
Section: Human Studies or Clinical Trials Of Nanostructures For Diffementioning
confidence: 99%
“…According to preliminary comparison studies with SUPRATHEL, epithelialization rate was faster with nanofibrillar cellulose dressing. 158 Recently, the bone healing tendency of a nanocomposite (DBSint) constituted of biomimetic nanostructured Mg-hydroxyapatite and human demineralized bone matrix was approved for clinical use. The clinicalradiographic and histomorphometric analysis in subjects undergoing high tibial osteotomy validated the safe and effective usage of these nanocomposites.…”
Section: Human Studies or Clinical Trials Of Nanostructures For Diffementioning
confidence: 99%
“…The optimal wound dressing is still under debate, with no international consensus [13]. For instance, mesh gauzes based on paraffin, synthetic dressings imitating the natural epithelium (Suprathel; Polymedics Innovations Inc., Woodstock, GA, USA) [14], or nanofibrillar cellulose wound dressings [15] enhance STSG donor site healing. Of interest, the latter exhibits a renewable nature, good biocompatibility, and excellent physical properties, and may be a promising candidate for clinical application.…”
Section: Vascularization In Skin Reconstructionmentioning
confidence: 99%